Minimum Horizontal Curve Radius and Curve Speed Limit of Single-axle Monorail Train Lines Based on Ride Comfort - DU Zixue; PI Yang; YANG Zhen (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To address the issues of poor operational stability and ride comfort in the actual operation of single-axle monorail trains, it is aimed to investigate the rational values of minimum horizontal curve radius and curve speed limit for single-axle monorail trains from the perspective of track alignment. [Method] A vehicle-track coupled dynamics model for the single-axle monorail train is established, and the model′s validity is verified. The evaluation methods for operational stability and ride comfort of monorail trains are introduced. Based on requirements for different ride comfort levels, a recommended value range for the minimum horizontal curve radius of single-axle monorail train lines is proposed. The rationality of recommended value ranges is verified through simulation analysis. To achieve the coordinated alignment of track and curve-passing speed, the speed limit of single-axle monorail train in small-radius curve sections is further investigated. [Result & Conclusion] For a given design speed, the minimum horizontal curve radius of the line is primarily determined by the maximum over-height angle in the curve section and the unbalanced allowable train lateral vibration acceleration. When the train operating speed is less than or equal to 80 km/h, the minimum horizontal curve radius of 320 m for a single-axle monorail train line is adopted, together with a train operating speed limit of 4.30R(where R is the curve radius) in small-radius curve sections.